2014
DOI: 10.11648/j.jfns.20140206.16
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Physico-Chemical Properties of Pomegranate (punica granatum L.) Fruits of Dar es Salaam Tanzania

Abstract: Abstract:The physicochemical composition of pomegranate (Punica granatum L.) fruits from Kimara, Dar es Salaam during open air storage ripening process were determined. The ash, titratable acidity, crude fat, crude fiber, moisture and sugars content were determined by proximate analysis. Ascorbic acid contents were determined using the 2,6-dichlorophenol-indophenol dye method while mineral elements and heavy metals were determined by Flame Atomic Absorption Spectrophotometry (FAAS). The fruits were always harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
2
4
1
Order By: Relevance
“…In addition, increase in moisture content (%) reduces the proximate principles such as fat, protein and carbohydrate. thereby decreasing the energy value [26]. The obtained results were generally comparable to those reported in literature previously with some variations related to fruit variety and agroclimatic and environmental conditions.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, increase in moisture content (%) reduces the proximate principles such as fat, protein and carbohydrate. thereby decreasing the energy value [26]. The obtained results were generally comparable to those reported in literature previously with some variations related to fruit variety and agroclimatic and environmental conditions.…”
Section: Resultssupporting
confidence: 90%
“…Different studies have shown the variations in ash contents (%) in different fruits. High total ash content (%) for a food material signifies the presence of adulterants [26]. For determination of ash contents (%), crucibles were dried in a microwave oven at 90 ºC until constant weight and then transferred into the desiccators to cool down.…”
Section: Resultsmentioning
confidence: 99%
“…Pomegranate (Punica granatum, L.) is widely cultivated in several parts of the world and its fruit has attracted huge interest among scientists and consumers worldwide, due to both their chemical and phytochemical composition and sensory value. [1][2][3] The edible parts of the pomegranate fruit are arils and seeds. Arils contain water, sugars (mainly fructose and glucose), organic acids, such as ascorbic, citric, and malic acid, and bioactive compounds such as phenolics and flavonoids, and principally anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate ( Punica granatum , L.) is widely cultivated in several parts of the world and its fruit has attracted huge interest among scientists and consumers worldwide, due to both their chemical and phytochemical composition and sensory value 1–3 . The edible parts of the pomegranate fruit are arils and seeds.…”
Section: Introductionmentioning
confidence: 99%
“…as an indicator, 10 mL of the filtrate was titrated with 0.1 M of NaOH using a 1% phenolphthalein solution. The outcomes were proved as % citric acid (Lugwisha Esther Hellen, Fabian Christina, & Othman, 2014). All measurements were performed in triplicate and the average marks were noted.…”
Section: Titratable Aciditymentioning
confidence: 99%